Castleman disease with synchronous primary rectal and prostate cancers: a case report of successful multimodal treatment and 2-year recurrence-free survival - Zheng, Linhai; Lu, Mudan; Liu, Yiming; Qiu, Zijian (Frontiers in Oncology, 2025)
BackgroundCastleman disease (CD) is a rare lymphoproliferative disorder associated with immune dysregulation that may increase the risk of malignancy. Synchronous multiple primary cancers are uncommon, and their etiology remains largely unclear. The coexistence of CD with synchronous multiple primary malignancies is exceptionally rare; therefore, the underlying mechanisms and optimal treatment strategies deserve further investigation.Case PresentationA 72-year-old male was diagnosed with Castleman disease in the hepatogastric space concomitant with synchronous primary rectal and prostate cancers. The patient underwent resection of the Castleman lesion, followed by four cycles of neoadjuvant FOLFOX chemotherapy for rectal cancer, simultaneous external beam radiotherapy for both rectal and prostate cancers, a Dixon procedure for rectal cancer, and three cycles of adjuvant FOLFOX chemotherapy. During a 2-year follow-up period, serial measurements of total and free prostate-specific antigen (PSA) remained within normal limits, and contrast-enhanced computed tomography (CT) revealed no evidence of recurrence or metastasis. The patient remains clinically stable.ConclusionThree tumors in the same patient are extremely rare. The comprehensive treatment plan, including surgery, neoadjuvant chemoradiotherapy, and endocrine therapy may serve as a useful clinical reference for managing similar cases.